2020
DOI: 10.1002/emp2.12169
|View full text |Cite|
|
Sign up to set email alerts
|

Determinants of emergency physician wellness in Belgium

Abstract: Objectives This cross‐sectional study examines first whether emergency physicians differ from a comparison group of surgeons, more specifically general surgeons and orthopedic surgeons, in terms of job and organizational characteristics and second to what extent these characteristics are determinants of professional well‐being outcomes in emergency physicians. Methods Belgian emergency physicians (n = 346) were invited to participate in this study. Forty‐three percent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Various research found that the social climate was a factor favoring the nurses' and physicians' intentions to stay with their employer, (Heponiemi et al, 2019;Martinussen et al, 2020;Nikkhah-Farkhani and Piotrowski, 2020) while the leadership style had a delicate influence on the physicians' intentions to leave. (Stagnitti et al, 2006;Suliman, 2009;Halter et al, 2017;Fontes et al, 2019;Pishgooie et al, 2019;Labrague et al, 2020;Lee and Jang, 2020;Magbity et al, 2020;Martinussen et al, 2020) Negative feelings when experiencing discrimination (Heponiemi et al, 2019), bullying (Adriaenssens et al, 2015;Edmonson and Zelonka, 2019;Park and Choi, 2019;Favaro et al, 2021), conflict with peers (Zaheer et al, 2019;Bautista et al, 2020;Lee and Kim, 2020), high workloads (Perkins et al, 2007;Bautista et al, 2020;Lee and Kim, 2020), understaffing (Sasso et al, 2019), emotional exhaustion (Hoonakker et al, 2013;Vandenbroeck et al, 2017;Sasso et al, 2019), long working shifts (Dall'Ora et al, 2015;Arslan Yürümezoğlu et al, 2019) and stress (Hoonakker et al, 2013;Halter et al, 2017;Lee and Jang, 2020;Somville et al, 2020;Chen et al, 2021) also push physicians' and nurses' intentions towards leaving their job behind. Further factors that previously affected the physicians' and nurses' job satisfaction also influence their intention to stay: fair pay…”
Section: Work Conditions Of Physicians and Nursesmentioning
confidence: 99%
“…Various research found that the social climate was a factor favoring the nurses' and physicians' intentions to stay with their employer, (Heponiemi et al, 2019;Martinussen et al, 2020;Nikkhah-Farkhani and Piotrowski, 2020) while the leadership style had a delicate influence on the physicians' intentions to leave. (Stagnitti et al, 2006;Suliman, 2009;Halter et al, 2017;Fontes et al, 2019;Pishgooie et al, 2019;Labrague et al, 2020;Lee and Jang, 2020;Magbity et al, 2020;Martinussen et al, 2020) Negative feelings when experiencing discrimination (Heponiemi et al, 2019), bullying (Adriaenssens et al, 2015;Edmonson and Zelonka, 2019;Park and Choi, 2019;Favaro et al, 2021), conflict with peers (Zaheer et al, 2019;Bautista et al, 2020;Lee and Kim, 2020), high workloads (Perkins et al, 2007;Bautista et al, 2020;Lee and Kim, 2020), understaffing (Sasso et al, 2019), emotional exhaustion (Hoonakker et al, 2013;Vandenbroeck et al, 2017;Sasso et al, 2019), long working shifts (Dall'Ora et al, 2015;Arslan Yürümezoğlu et al, 2019) and stress (Hoonakker et al, 2013;Halter et al, 2017;Lee and Jang, 2020;Somville et al, 2020;Chen et al, 2021) also push physicians' and nurses' intentions towards leaving their job behind. Further factors that previously affected the physicians' and nurses' job satisfaction also influence their intention to stay: fair pay…”
Section: Work Conditions Of Physicians and Nursesmentioning
confidence: 99%
“…Leadership style had a decisive influence on physicians' intentions to stay or to leave (Stagnitti et al, 2006;Suliman, 2009;Halter et al, 2017;Fontes et al, 2019;Pishgooie et al, 2019;Labrague et al, 2020;Lee and Jang, 2020;Magbity et al, 2020;Martinussen et al, 2020). Other factors pushing physicians' and nurses' intentions toward leaving their job were: Negative feelings when experiencing discrimination (Heponiemi et al, 2019), bullying (Adriaenssens et al, 2015;Edmonson and Zelonka, 2019;Park and Choi, 2019;Favaro et al, 2021), conflict with peers (Zaheer et al, 2019;Bautista et al, 2020;Lee and Kim, 2020), high workloads (Perkins et al, 2007;Bautista et al, 2020;Lee and Kim, 2020), understaffing (Sasso et al, 2019), emotional exhaustion (Hoonakker et al, 2013;Vandenbroeck et al, 2017;Sasso et al, 2019), long working shifts (Dall'Ora et al, 2015;Arslan Yürümezoglu et al, 2019), and high stress (Hoonakker et al, 2013;Halter et al, 2017;Lee and Jang, 2020;Somville et al, 2020;Chen et al, 2021). Several factors affecting job satisfaction also influence physicians' and nurses' intention to stay: Fair pay 10.3389/fpsyg.2023.1106501 (Kao et al, 2018), freedom to do the job (Barken et al, 2018), job autonomy (Stagnitti et al, 2006;Barken et al, 2018), and recognition …”
Section: Introduction 1determinants Of Job Satisfaction and Intention...mentioning
confidence: 99%
“…In, 1 the author wants to correct the authorship in the published article. The authorship should read:…”
mentioning
confidence: 99%